2003
DOI: 10.1097/00008390-200308000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Germline 657del5 mutation in the NBS1 gene in patients with malignant melanoma of the skin

Abstract: In this study we determined in what proportion of consecutive malignant melanoma (MM) cases the 657del5 mutation of exon 6 of the NBS1 gene can be detected and whether it is associated with the occurrence of MM. Two groups of patients were studied: a series of 80 consecutive patients with histologically confirmed MM of the skin diagnosed in the city of Szczecin, Poland, and a series of 530 consecutive individuals selected at random by family doctors from the city of Szczecin. Molecular examination included an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 22 publications
3
23
0
Order By: Relevance
“…Although a number of published reports have suggested that mutations in NBS1, especially 657del5, is associated with elevated risk for some cancers, including ovarian (13), breast (7,8,10), melanoma (7,9), and lymphoid malignancies (7,11,12), such findings have not been replicated in other studies (21)(22)(23)(24). For prostate cancer, Cybulski et al (5) found that the 657del5 mutation was a risk factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a number of published reports have suggested that mutations in NBS1, especially 657del5, is associated with elevated risk for some cancers, including ovarian (13), breast (7,8,10), melanoma (7,9), and lymphoid malignancies (7,11,12), such findings have not been replicated in other studies (21)(22)(23)(24). For prostate cancer, Cybulski et al (5) found that the 657del5 mutation was a risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…This founder mutation has been found with a high frequency in the Slavic population, which includes individuals primarily from Poland, Ukraine, and the Czech Republic. A number of studies suggest that heterozygosity for a mutation in NBS1 may be associated with elevated risk for some cancers (7)(8)(9)(10)(11)(12)(13), including prostate cancer (5). Cybulski et al (5) showed an increased risk for prostate cancer among carriers of the 657del5 mutation in both familial and non-familial cases from Poland.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that heterozygous carriers of the founder mutation of the NBS (657del5 allele) may be at increased risk of cancer, but prostate cancer specifically has not been studied to date (22)(23)(24)(25)(26)(27). In this study, we compared the frequency of the 657del5 mutation in unselected patients with sporadic and familial prostate cancer with that of a control group to determine whether NBS1 plays a role in the development of prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…(21) Recent studies strongly suggest that heterozygous 657del5 mutation carriers have an elevated risk of malignant tumor development, especially of melanoma, (22,23) colon and rectum cancer, (23) prostate cancer,…”
mentioning
confidence: 99%
“…(17) Heterozygous mutations in the NBS1 gene have been described in various groups of cancer patients, for example, patients with acute lymphoblastic leukemia (ALL), (18,19) non-Hodgkin's lymphoma (NHL), (20) and in cancer cell lines. (21) Recent studies strongly suggest that heterozygous 657del5 mutation carriers have an elevated risk of malignant tumor development, especially of melanoma, (22,23) colon and rectum cancer, (23) prostate cancer, (24) ovarian cancer, (25) breast cancer (26,27) and NHL. (28,29) The aim of our research was to assess whether mutations in the NBS1 gene may contribute to the development of larynx cancer (LC) and MPT of the head and neck.…”
mentioning
confidence: 99%